2005
DOI: 10.1124/jpet.105.096339
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of NCX4016 [2-Acetoxy-benzoate 2-(2-nitroxymethyl)-phenyl Ester] on the Consequences of Ischemia and Reperfusion in the Streptozotocin Diabetic Rat

Abstract: The aim of this study was to assess the effect of chronic administration of NCX4016 [2 acetoxy-benzoate 2-(2-nitroxymethyl)-phenyl ester], a nitric oxide-releasing aspirin derivative on the consequences of coronary artery occlusion in streptozotocin-diabetic rats. Rats were made diabetic by injection of streptozotocin (60 mg kg(-1)) and received insulin (2.5 U kg(-1) s.c.) daily for 4 weeks. Animals received vehicle (1 ml kg(-1) polyethylene glycol), aspirin (65.2 mg kg(-1)), NCX4016 (60 mg kg(-1)), or (iv) NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The present results clearly demonstrate that the 7-consecutive-day oral administration of NO-aspirin before myocardial ischemia offers noticeable cardioprotection by significantly limiting infarct size and/or lowering the mortality rate caused by 25 min of LCA occlusion followed by 48 h of reperfusion, which confirms previous infarct-limiting effects during early reperfusion (5,36,46). Moreover, the NO-aspirin improved part of cardiac dysfunctional recovery was noted at 48 h of reperfusion.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The present results clearly demonstrate that the 7-consecutive-day oral administration of NO-aspirin before myocardial ischemia offers noticeable cardioprotection by significantly limiting infarct size and/or lowering the mortality rate caused by 25 min of LCA occlusion followed by 48 h of reperfusion, which confirms previous infarct-limiting effects during early reperfusion (5,36,46). Moreover, the NO-aspirin improved part of cardiac dysfunctional recovery was noted at 48 h of reperfusion.…”
Section: Discussionsupporting
confidence: 74%
“…However, these cardioprotective effects against postischemic reperfusion injury are limited to 2-3 h, as shown by employing triphenyltetrazolium chloride (TTC) staining to assess infarcted myocardium. Our present interest is whether NO-aspirin only delayed the progression of reperfusion injury during early reperfusion in the studies reported (5,36,46), because, to our knowledge, rats subjected to acute myocardial infarction (AMI) develop severe inflammation a few hours postsurgery and reach maximum injury/mortality by the next morning. Furthermore, in the setting of brief ischemia followed by reperfusion, we are interested in whether the reduction in TTC-negative tissue observed in early reperfusion signifies genuine reduction of eventual infarct size following extended reperfusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, naproxcinod and NCX‐4016 were shown to reduce blood pressure in hypertensive rats, while no alteration of blood pressure in normotensive animals was reported for aspirin and flurbiprofen prodrugs . Second, naproxcinod and NCX‐4016 were able to reduce myocardial damage induced by ischemia/reperfusion in animal experiments . Third, NCX‐4016 has exhibited antiatherosclerotic actions in rodent studies .…”
Section: Association Of Nsaids With Protective Mediatorsmentioning
confidence: 99%
“…This concept, using a nitroaspirin compound from Nicox (NCX-4016) has subsequently been confirmed both in preclinical studies [488][489][490][491] and in clinical trials [492][493][494]. It is noteworthy that this compound appears to have pharmacological effects in models where the parent molecule (aspirin) is without marked effects, such as in animal models of myocardial ischemia-reperfusion [495] and vascular restenosis in hypercholesterolemia [496][497][498]. The potential clinical utility of the latter approach may be underlined by a recently completed clinical trial demonstrating the clinical effectiveness of NCX-4016 in patients with intermittent claudications [499].…”
Section: Combined No Donorsmentioning
confidence: 95%